The bankable SOE commercial financing for state-owned enterprises. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
ADB is committed to SOE reform that supports access to commercial finance in its developing member countries, as also emphasized in Strategy 2030. With the rise of commercial finance for SOEs, this publication details the steps to enhance the bankability of SOEs. It also explains how the risks of such borrowing, including defaults and moral hazards created by implicit guarantees, can be managed.
Keywords: Corporations -- Finance; Business enterprises -- Finance; Corporations -- Finance -- Management; Electronic book